Kualitas Pelayanan Laporan Polisi Model C pada Sentra Pelayanan Kepolisian Terpadu Resor Metro Tangerang Kota - Chandra Tirtana, Reza; Khoirul Anwar, Muhammad (Policy, Law and Political Research Center, 2023)
The Tangerang City Metro Police SPKT Unit as one of the agencies serving the community is required to have adequate quality. The problem that arises is the lack of quality of service at the Tangerang City Metro Police SPKT which is characterized by inadequate facilities. The purpose of this study is to analyze the quality of the Model C Police Report service at the Integrated Police Service Center for the Tangerang City Metro Resort in providing services to the community. This research uses a qualitative method and data collection using observation, interviews and documents. Data analysis in this research uses the service quality dimensions namely Tangible, Reliability, Responsiveness, Assurance, and Emphaty. Based on the results of data analysis and discussion of the research that has been carried out, it can be concluded that the services provided by SPKT Polres Tangerang Metro Kota are not good enough because there are still deficiencies in the indicators in each dimension, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy.